TALENT MANAGEMENT-BASED STATE CIVIL APPARATUS CAREER DEVELOPMENT - R. Taqwaty Firdausijah (Jurnal Info Sains : Informatika dan Sains, 2023)
Civil servant career development through talent management is an entity that is prioritized by the government. Talent management is a strategic approach to identifying, developing, and retaining individuals with exceptional potential and performance for critical organizational positions. The purpose of this study is to investigate and describe talent management-based state civil apparatus (ASN) career development in the context of a contemporary public service system. This study employs a qualitative approach and descriptive methodologies. The study's findings indicate that the Implementation of Talent Management adheres to the merit system's objective, planned, transparent, timely, accountable, political intervention-free, and KKN-free principles. Talent development in ASN is carried out through three main approaches: career acceleration, competency development, and qualification improvement. Although talent management-based ASN career development sounds good, there are several inhibiting factors that need to be addressed, such as leadership commitment and less than optimal follow-up assessments. It takes strong leadership commitment and policies in implementing a merit system and proper follow-up on ASN assessment results so ASN career development can run well.